2014
DOI: 10.1027/1618-3169/a000263
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Efficiency Is Greater for Human Faces Compared to Animal Faces

Abstract: The Animate Monitoring Hypothesis proposes that humans and animals were the most important categories of visual stimuli for ancestral humans to monitor, as they presented important challenges and opportunities for survival and reproduction; however, it remains unknown whether animal faces are located as efficiently as human faces. We tested this hypothesis by examining whether human, primate, and mammal faces elicit similarly efficient searches, or whether human faces are privileged. In the first three experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 68 publications
3
21
0
Order By: Relevance
“…Another study found differences in infants' sensitivity to gaze in human and nonhuman stimuli: 12‐month‐olds looked longer to, and were better at gaze following, when observing videos of humans compared to apes (Kano & Call, ). We also found our infants looked longer to human than animal faces (Prediction 3b), consistent with studies in adults, reporting privileged detection of conspecifics (Simpson, Buchin, et al, ; Simpson, Husband, Yee, Fullerton, & Jakobsen, ; Stein, Sterzer, & Peelen, ). Our findings of an early own‐species bias suggest that infants have already specialized for processing conspecific faces by 2 to 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
“…Another study found differences in infants' sensitivity to gaze in human and nonhuman stimuli: 12‐month‐olds looked longer to, and were better at gaze following, when observing videos of humans compared to apes (Kano & Call, ). We also found our infants looked longer to human than animal faces (Prediction 3b), consistent with studies in adults, reporting privileged detection of conspecifics (Simpson, Buchin, et al, ; Simpson, Husband, Yee, Fullerton, & Jakobsen, ; Stein, Sterzer, & Peelen, ). Our findings of an early own‐species bias suggest that infants have already specialized for processing conspecific faces by 2 to 6 months of age.…”
Section: Discussionsupporting
confidence: 90%
“…Given the social and ecological importance of faces for infants, and their early exposure to conspecifics, biases to detect conspecific faces may be evident in the first year of life (Simpson et al, 2015). In adults, conspecific faces are detected more efficiently than heterospecific faces (Simpson et al, 2014a;2014c). The present study explored whether this OSB in face detection is present in 6-and 11-month-old infants.…”
Section: Discussionmentioning
confidence: 91%
“…Each array contained a unique neutral face of a human, non-human primate (hereafter "primate"), or nonprimate mammal (hereafter "mammal"). Faces were upright with visible and open eyes, visible noses and mouths, and were neutral expressions (Simpson et al, 2014a;Simpson, Mertins, Yee, Fullerton, & Jakobsen, 2014c). The remaining images were unique man-made and natural items.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we assessed attention prioritization to faces in displays with multiple distractors with three discrete aspects of visual attention, extracted from eye tracking data: (a) detection , or the likelihood of fixating on a stimulus (e.g., Adler & Oprecio, ; Amso, Haas, & Markant, ; Franklin, Pilling, & Davies, ; Jakobsen, Umstead, & Simpson, ; Sasson, Turner‐Brown, Holtzclaw, Lam, & Bodfish, ; Simpson, Mertins, Yee, Fullerton, & Jakobsen, ), also referred to as face foraging (Elsabbagh et al., ) or accuracy (Hershler & Hochstein, ; Tomonaga & Imura, ); (b) attention capture , or the extent to which a stimulus spontaneously elicits attention, measured as the speed or response time (RT) to fixate on a target (e.g., Adler & Gallego, ; Adler & Oprecio, ; Franklin et al., ; Jakobsen et al., ; Simpson, Buchin, Werner, Worrell, & Jakobsen, ); and (c) attention holding , the duration of looking at images, also called dwell time or perseveration , which reflects attention maintenance, a proxy of interest (Chevallier et al., ; Di Giorgio, Méary, Pascalis, & Simion, ; Di Giorgio, Turati, Altoè, & Simion, ; Elsabbagh et al., ; Gluckman & Johnson, ; Jakobsen et al., ; Sasson et al., ). Although related, these attentional mechanisms—detection, attention capture, and attention holding—make up attentional efficiency and reflect fundamental aspects of visual processing (Cohen, ); therefore, together these measures provide a more complete picture of attention allocation.…”
mentioning
confidence: 99%